Unveiling the potential of lactic acid bacteria from Algerian dromedary camel milk: diversity, technological applications, and antimicrobial insights - Latreche, Bilal; Bendjama, Esma; Loucif, Lotfi; Sanah, Ibtissem; Messaoudi, Mohammed; Bensouici, Chawki; Djeghim, Fairouz; Kerbab, Khawla; Rolain, Jean-Marc; D’Elia, Maria; Rastrelli, Luca; Becila, Samira (Frontiers in Nutrition, 2025)
BackgroundLactic acid bacteria (LAB) play a central role in the food industry due to their ability to produce beneficial metabolites and enhance the technological and sensory qualities of fermented products. Additionally, they contribute to human health by supporting immune function and maintaining gut microbiota balance through probiotic effects. This study aimed to isolate and characterize LAB from dromedary camel milk (DCM) collected in semi-arid regions of Algeria, evaluating their technological functionalities and antimicrobial activities.MethodsA total of 31 LAB strains were isolated from raw DCM samples. Strains were identified using MALDI-TOF MS and characterized for acidification kinetics, lipolytic, proteolytic, and amylolytic activities, exopolysaccharide (EPS) and acetoin production, and antimicrobial properties against common foodborne pathogens.ResultsFour species were identified, with Enterococcus italicus reported for the first time in this environment. Significant inter-strain variability (p < 0.0001) was observed in all tested properties. Three strains (BLC9, BLC12, BLC14) acidified milk rapidly to pH 4.6 within 12 h. Proteolytic activity was detected in 87.10% of strains, while EPS and acetoin were produced by 29.03 and 48.39%, respectively. Lipolytic and amylolytic activities were generally weak. Notably, 74.19% of the strains exhibited antimicrobial activity, inhibiting at least one pathogen, with inhibition zones varying significantly (p < 0.0001).ConclusionDromedary camel milk from Algerian semi-arid regions represents a rich source of LAB strains with promising technological and antimicrobial potential. These native isolates could be further developed for use in additive-free fermented foods and natural biopreservation systems, supporting sustainable and functional food innovation.